Moderasi Organizational Embeddedness Pada Pengaruh Organizational Trust Terhadap Workplace Deviance - Handayani, Ririn; Nurendari , Indah Pratiwi; Bastian, Adolf (CV. ITTC INDONESIA, 2024)
This study aims to analyze and prove the effect of organizational trust on workplace deviance and prove the role of organizational embeddedness in moderating the effect of organizational trust on workplace deviance. This research uses Path Analysis. Organizational Trust has a significant negative effect on Workplace Deviance. In this context, the higher the level of Organizational Trust felt by employees, the lower the level of deviant behavior in the workplace. Although Organizational Trust has a significant effect on Workplace Deviance, the results of hypothesis testing show that Organizational Embeddedness does not moderate this relationship. Organizational Embeddedness, which includes fit, relationship, and sacrifice in the organization, does not affect the strength or direction of the relationship between Organizational Trust and Workplace Deviance. Thus, interventions aimed at increasing Organizational Trust may directly impact the reduction of Workplace Deviance without the need to consider employees' level of Organizational Embeddedness. Although Organizational Embeddedness does not moderate this relationship, this finding confirms that employees' trust in the work team, work environment, and management is a major factor that needs to be considered by leaders. Thus, efforts to increase trust should be prioritized in human resource management strategies to create a positive work environment.